Cabozantinib versus everolimus in advanced renal cell carcinoma - Choueiri, Toni K. (N Engl J Med, 2015)
BACKGROUND: Cabozantinib is an oral small molecule tyrosine kinase inhibitor that targets vascular endothelial growth factor receptor (VEGFR) as well as MET and AXL; each has been implicated in metastatic renal cell carcinoma (RCC) pathobiology or development of resistance to antiangiogenic drugs. This randomized open-label phase 3 trial evaluated the efficacy of cabozantinib compared to everolimus in RCC patients who progressed after VEGFR-targeted therapy. METHODS: The trial randomized 658 patients to receive cabozantinib at a dose of 60 mg daily, or everolimus at a dose of 10 mg daily. The primary endpoint was progression-free survival. Secondary efficacy endpoints were overall survival and objective response rate. RESULTS: Median progression-free survival was 7.4 months with cabozantinib and 3.8 months with everolimus. The risk of progression or death was 42% lower with cabozantinib compared to everolimus (hazard ratio, 0.58; 95% confidence interval [CI] 0.45 to 0.75; P < 0.001). Objective response rates were 21% with cabozantinib and 5% with everolimus (P < 0.001). A planned interim analysis showed that overall survival was improved with cabozantinib (hazard ratio, 0.67; 95% CI, 0.51 to 0.89; P = 0.005) but did not cross the significance boundary. Adverse events (grade 3 or 4, regardless of causality) were reported in 74% of cabozantinib patients and 65% of everolimus patients. Discontinuation of study treatment for adverse events occurred in 9.1% of cabozantinib patients and 10% of everolimus patients. CONCLUSIONS: Cabozantinib improved progression-free survival compared to everolimus in RCC patients who progressed after VEGFR-targeted therapy.